Status Nutrisi Pada Anak Dengan Gangguan Ginjal Kronis: Literatur Review - IGA Dewi Purnamawati (AKPER Pasar Rebo, 2021)
Background: Malnutrition is a common complication in children with Chronic Kidney Disease (CKD), adequate nutrition will promote normal growth and development and regular evaluation of nutritional status is a key point in the management of children with CKD. Objective: to identify through a literature study the nutritional status of children with CKD. Methods: literature review through database searches: Gogle Scholar, Proquest, EBSCO, ClinicalKey Nursing database from 2018 to 2021. Selected studies with criteria regarding assessment of nutritional status, evaluation of nutritional status, growth in children with CKD who have undergone hemodialysis or peritoneal dialysis. Results: Nine studies were included in the review and provided an overview of the poor nutritional status of children with CKD. Overview of height, weight, Mid-arm circumference (MAC), Triceps Skinfold Thickness (TSFT) is less, small upper arm circumference, low body mass index and decreased HDL cholesterol, hypoalbumin, anemia, vitamin A, C deficiency, D, hypocalcemia, hypokalemia and hypercreatinemia, elevated cholesterol and hypertriglyceridemia. Conclusion: the nutritional status of children with CKD is a problem faced by children with multifactors so that a continuous monitoring of the nutritional status of children is needed to prevent severe nutritional disorders.